AN ANALYSIS OF TRANSLATION TECHNIQUES USED IN TRANSLATING SIMILE IN THE NOVEL:"THE BROKEN WINGS" BY TWO DIFFERENT TRANSLATORS - Andri Turmuzi, - (2011)
This research entitled An Analysis of Translation Techniques Used in Translating Simile in the Novel: "The Broken Wings" by Two Different Translators examines the comparison of techniques in translating simile figurative language of The Broken Wings novel by two different translators. This research used qualitative descriptive method to describe the quality of the materials. Both translated novels are analyzed by using Molina and Albir's (2002:509-511) theory on techniques of translation analysis. The novels researched are those written in English as the source text-The Broken Wings; in Bahasa Indonesia, first-Sayap-sayap Patah translated by M. Ruslan Shiddieq, and second-Sayap-sayap Patah translated by Sabri. Based on this research, the researcher found 134 explicit similes and 43 implicit similes as figurative language used in the novel. Concerning translation technique, literal translation technique is mostly used by both translators in translating similes, respectively 135 times by M. Ruslan Shiddieq, and 84 times by Sabri. In addition, M. Ruslan Shiddieq only applied nine translation techniques, while Sabri applied 11 translation techniques. Most of the translation techniques are appropriate to use and make sense in the target language, particularly literal translation technique, because they fulfill the criteria of good translation, such as accuracy, clarity, and naturalness (Larson, 1984:485). The above criteria is applied by both translators to produce good quality of translated novels entitled Sayap-sayap Patah.